Trace-mineral salt for steers on a fattening ration (Concrete and shelter vs. dirt and no shelter) with observations on shrink - Koch, B.A.; Smith, E.F.; Richardson, D.; McCartor, M.M. (Kansas Agricultural Experiment Station, 2011)
Previous data reported from this station seem to indicate that supplemental dietary trace minerals may be valuable under certain feeding conditions. Those data also indicated that trace minerals might be related to weight loss during shipping. This study was designed to further determine the value of supplemental dietary trace minerals when cattle were on concrete and had shelter available and when they were on dirt with no shelter.
Keywords: Beef; Trace-mineral salt; Shrink; Temperature